2010
DOI: 10.1071/an09123
|View full text |Cite
|
Sign up to set email alerts
|

Influence of divergent selection for reproduction on the occurrence of breech strike in mature Merino ewes

Abstract: Divergent selection resulted in Merino lines that differ markedly for reproduction. These lines were selected from the same base population from 1986 to 2009. Selection was initially based on maternal ranking values for reproduction in both ewe and ram progeny. The maternal ranking scores were augmented by breeding values from a single-trait repeatability model since 2003. The site and severity of flystrike were recorded for mature breeding ewes in the flock from 2007 to 2009. The following details were captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Negative genetic correlations between NLB1 and TOT (Table 7) suggested that plainer ewes are more likely to have multiples. This is important for the South African Merino industry as plainer sheep are more desirable because of their faster growth and higher lambing percentages (Olivier & Cloete, 1998) and reduced chances of contracting fly strike (Baillie, 1979;Scholtz et al, 2010). Genetic trends in the resource flock used in the present study also suggested that the progeny of the line selected for an improved reproduction became heavier and plainer over time (Cloete et al, 2005).…”
Section: Resultsmentioning
confidence: 53%
“…Negative genetic correlations between NLB1 and TOT (Table 7) suggested that plainer ewes are more likely to have multiples. This is important for the South African Merino industry as plainer sheep are more desirable because of their faster growth and higher lambing percentages (Olivier & Cloete, 1998) and reduced chances of contracting fly strike (Baillie, 1979;Scholtz et al, 2010). Genetic trends in the resource flock used in the present study also suggested that the progeny of the line selected for an improved reproduction became heavier and plainer over time (Cloete et al, 2005).…”
Section: Resultsmentioning
confidence: 53%
“…Divergent selection for reproductive traits resulted in lines that differ in the reproduction traits selected for, namely number of lambs weaned and weight of lamb weaned per ewe mated (Cloete et al, 2004), lamb survival , susceptibility to breech strike (Scholtz et al, 2010), behaviour (Cloete et al, 2005; and adrenal function (Van der Walt et al, 2009;Hough et al, 2015). In all these studies, the H-line showed superior ability to reproduce and survive, resist breech strike, and adapt to stressful situations, compared with the L-line.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the selection procedure for the resource flock and experimental site have been documented in the literature (Cloete & Scholtz, 1998;Cloete et al, 2004;Scholtz et al, 2010). Briefly, two lines of sheep that differ in reproductive performance were developed from 1986.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of significant genetic variation in breech strike is supported by marked line differences in its frequency in lines of Merino sheep divergently selected for number of lambs weaned per ewe joined (Scholtz et al, 2010a). The frequency of breech strike in more wrinkly animals selected against reproduction rate was between fourfold and tenfold higher than in plainer animals selected for an improved reproduction rate.…”
Section: Resistance To Stressorsmentioning
confidence: 88%